Stratospheric climate anomalies and ozone loss caused by the Hunga Tonga-Hunga Ha'apai volcanic eruption - Wang, Xinyue (author); Randel, William (author); Zhu, Yunqian (author); Tilmes, Simone (author); Starr, Jon (author); Yu, Wandi (author); Garcia, Rolando (author); Toon, Owen B. (author); Park, Mijeong (author); Kinnison, Douglas (author); Zhang, Jun (author); Bourassa, Adam (author); et al. (Journal of Geophysical Research: Atmospheres, 2023)
The Hunga Tonga-Hunga Ha'apai (HTHH) volcanic eruption in January 2022 injected unprecedented amounts of water vapor (H2O) and a moderate amount of the aerosol precursor sulfur dioxide (SO2) into the Southern Hemisphere (SH) tropical stratosphere. The H2O and aerosol perturbations have persisted during 2022 and early 2023 and dispersed throughout the atmosphere. Observations show large-scale SH stratospheric cooling, equatorward shift of the Antarctic polar vortex and slowing of the Brewer-Dobson circulation. Satellite observations show substantial ozone reductions over SH winter midlatitudes that coincide with the largest circulation anomalies. Chemistry-climate model simulations forced by realistic HTHH inputs of H2O and SO2 qualitatively reproduce the observed evolution of the H2O and aerosol plumes over the first year, and the model exhibits stratospheric cooling, circulation changes and ozone effects similar to observed behavior. The agreement demonstrates that the observed stratospheric changes are caused by the HTHH volcanic influences. 1852977 80NSSC20K0928